2017
DOI: 10.11648/j.ajbes.20170301.11
|View full text |Cite
|
Sign up to set email alerts
|

Threats, Use and Management Interventions for Restoration of Lake Chitu West Arsi, Ethiopia

Abstract: Lake Chitu is one of Ethiopian Flamingo Lakes known by single dominant blue green algal specie calledArthrospira fusiformis. A household questionnaire survey of respondents, key informants and focus group discussion were made in 2012 in Labu Subuqa kebele where lake Chitu is found to see major threats for general ecosystem disturbance, to see the use of the lake for the surrounding community and to identify major stakeholders for restoration and conservation of the lake in an integrated way. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The livelihood of respondents in both the study areas is mainly based on agriculture and it is of mixed crop livestock production system. This result is in line with earlier reports that mixed agriculture is the major livelihood activity (72.5%) of people living around Chitu Lake and the contribution of livestock in supporting the livelihood of lake community is of paramount importance [31].…”
Section: Discussionsupporting
confidence: 92%
“…The livelihood of respondents in both the study areas is mainly based on agriculture and it is of mixed crop livestock production system. This result is in line with earlier reports that mixed agriculture is the major livelihood activity (72.5%) of people living around Chitu Lake and the contribution of livestock in supporting the livelihood of lake community is of paramount importance [31].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, samples of Lake Chitu and Lake Abijata shared the highest number of prokaryotic OTUs, while in previous studies, a higher overlap of OTUs was observed between Lake Shala and Lake Abijata ( Lanzén et al, 2013 ). This discrepancy in overlaps might result from the fourfold salinity increment in Lake Abijata, which is a higher increase than in the other Ethiopian soda lakes over the last three decades ( Ayenew and Legesse, 2007 ; Klemperer and Cash, 2007 ; Faris, 2017 ). During the last three decades, the surface area of Lake Abijata has decreased by more than 50% and the average depth by 5 m as a result of the abstraction of water for soda ash production by the Abijata-Shala Soda Ash Factory and the diversion of the lake’s feeder rivers, Horakelo and Bulbula, for irrigation ( Ayenew and Legesse, 2007 ; Simachew et al, 2016 ).…”
Section: Discussionmentioning
confidence: 95%
“…The East African Rift Valley soda lakes are among the world’s most productive aquatic systems with primary production rates exceeding 10 g C m −2 day −1 ( Grant and Jones, 2016 ), providing abundant organic matter supporting a diverse group of microorganisms. Lake Chitu is the most productive among the three lakes, having thick biomass of the blue-green algae, Arthrospira fusiformis ( Faris, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, approximately 4% of the GHs in this investigation belonged to GH13, which encodes amylases. The Ethiopian soda lakes are known to have one of the highest primary productivity of any natural habitat due to the thick biomass of cyanobacteria ( Faris, 2017 ), which frequently accumulate starch (10–50%) as part of their biomass ( Möllers et al, 2014 ). Therefore, these heterotrophic microorganisms are known to produce abundant hydrolytic enzymes, such as amylases, to allow the breakdown of starch ( Sorokin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%